A review of the design aspects of ground heat exchangers - Aresti, Lazaros; Christodoulides, Paul; Florides, Georgios A. (My University, 2018)
The advancement of technology and renewable energy systems (RES) have evolved considerably through the years. Geothermal energy was first introduced in Italy in 1904 and has ever since dramatically increased in efficiency. One of the main types of RES, Ground Source Heat Pumps (GSHPs), are used for heating and cooling a space when coupled with Ground Heat Exchangers (GHEs). GSHPs extract or reject heat to the Earth via a network of tubes. The closed loop system, either vertical or horizontal, is the most common of the configurations. Alternatively, pipes can run all the way down to utilize natural underground water sources, when present, in an open loop configuration. GHEs have significantly higher performance over conventional air-to-air heat exchanger systems and the reduction of their cost and the improvement of their overall efficiency through their design are crucial in research. In this paper are presented and reviewed the design aspects of GHE systems. In particular are discussed the types of GHEs such as open or closed loop systems, vertical or horizontal, U-tube or spiral, energy piles and hybrid systems. A comparative analysis through the literature of the various geometrical aspects of GHEs and the geothermal investigation of the ground environment and the materials used in the construction of GHEs are also presented. Then is analyzed the modeling – experimental and mathematical – of GHEs, with terms that have been extensively studied, like borehole thermal resistance, thermal characteristics, thermal response test, line-source and cylindrical-source models, discussed in detail. Next a demonstration of designing a numerical model of a GHE system through a software, taking into consideration the thermal characteristics, is given. Finally, a comparative detailed list in the form of a table of more than 30 mathematical and/or experimental GHE studies is provided, focusing on the important factors analyzed and findings of each. The overall aim of the current review study is to help improve the efficiency and the total manufacturing cost of GHEs.
Keywords: Ground Heat Exchanger; Energy piles; Geothermal investigation; Thermal response test; Line-source model; Cylindrical-source model